Interface Deformable, Thermally Sensitive Hydrogel–Elastomer Hybrid Fiber for Versatile Underwater Sensing. Issue 12 (9th November 2020) - Wang, Chengmin; Wu, Baohu; Sun, Shengtong; Wu, Peiyi
Abstract: Underwater sensing plays a vital role in perceiving various hydrodynamic stimuli for underwater operations, while fishes evolve an adaptable, durable, and multifunctional lateral line sensory system to feel mechanical deformations from nearly all sources as well as water temperature changes. Such perfect integration of multiple functions into one biological system poses a great challenge for artificial soft sensors. Here, by constructing a stretchable and water‐proof core‐cladding hydrogel–elastomer hybrid optical fiber, nearly all the underwater sensations of fish lateral lines can be realized with unprecedented sensing stability. High‐refractive‐index salt, LiBr, is introduced to the hydrogel core to enable long‐range light propagation with a low loss coefficient (≈ 0.32 dB cm −1 ), and the dissimilar yet tightly adhered hydrogel–elastomer interface is readily deformable, contributing to the ultrasensitive optical response to subtle environmental stimulations, induced by either motions, hydrostatic pressure variations, ultrasonic/audible sound waves, or water flows. Moreover, the optical loss of the hybrid fiber is linearly responsive to wide temperature changes (5–70 ° C), caused by the altered light scattering from hydrogel chain clustering. The present elastomer–hydrogel hybrid optical fiber offers a new designing strategy in developing next‐generation underwater stretchable ray‐optic sensors. Abstract : Inspired by the multiple sensory functions of fish lateral lines to perceive various hydrodynamic stimuli, a highly stretchable, step‐index hydrogel–elastomer hybrid optical fiber is designed. Owing to the merits of easy deformation, readily distorted hydrogel–elastomer interface, and temperature‐induced hydrogel chain clustering, the fiber can mimic nearly all the underwater sensations of fish lateral lines with high sensing stability.